Capacitación electoral acerca del voto facultativo como mecanismo de fortalecimiento a la democracia en jóvenes de la parroquia Malacatos - Eras Robles, Lisbeth Maricely (2022)
This research analyzed the electoral training as a mechanism to strengthen democracy through key institutions in the process such as the National Electoral Council with the purpose of generating awareness among young voters in the Malacatos parish, where participation rates in previous elections were analyzed and their low participation was observed, likewise the advantages and disadvantages of young people and other optional voters to attend voting were analyzed where it was mentioned that it is important that they participate, but disadvantages are generated from the fact that for several factors this vote is violated. Surveys were also conducted to see how the electoral behavior they could have in elections, which yielded accurate results about being influenced by the attractive proposals that candidates make in elections, they also mentioned that they might not exercise their right to vote due to lack of knowledge or interest, it was also observed that they consider electoral training as an informative means at the time of reasoning their vote, Thus, generating the possible problems on which the electoral training would focus, talking about encouraging young people to be interested in making decisions at the polls, knowledge of the proposals, considering their possible ideological inclination in order to form from the classrooms future men and women capable of providing a conscious vote and empowering decision making for the good of the country providing legitimacy to the rulers through democracy